Soil fertility status of rehabilitated forest soil in Bintulu, Sarawak after 30 years of planting - Jamaluddin, Aiza Shaliha; Ibrahim, Zahari; Karam, Daljit Singh; Rajoo, Keeren Sundara; Jusop, Shamshuddin; Gandaseca, Seca; Abdu, Arifin (Malaysian Society of Soil Science, 2022)
Rehabilitation of degraded forestland is critical because it aids in reducing soil nutrient loss, improving vegetation stand and/or composition, and addressing environmental concerns. Thus, the purpose of this study was to determine the soil fertility condition in soils in rehabilitated forests after 30 years of planting. This study was conducted in 16 plots of a 47.5-hectare rehabilitated forest at Universiti Putra Malaysia Bintulu Campus in Sarawak, Malaysia. As of 2010, around 350,000 seedlings from 128 Sarawak native species had been planted. Soil samples were taken from different depths at each site (0-15 cm and 15-30 cm). Soil chemical properties were determined using standard laboratory methods while soil compaction analysis was determined using the fall-corn-type soil penetrometer (Hasegawa Type H-60). Soil Fertility Index (SFI) and the Soil Evaluation Factor (SEF) were used to estimate soil fertility and site quality. The compaction rate for the soil at rehabilitated forest plots was inversely proportional to cumulative depth. The compaction rates for plots in years 1991 to 2000 showed an increase in compaction rates with the depth of soil. The total cumulative depth for plots 2001 to 2008 had a longer graph trend compared to the previous years. The principal component analysis (PCA) showed that pH, OM, exchangeable Mg, CEC, and available P all contributed positively to factor loading in PC1. Our data showed a moderately positive correlation between CEC and exchangeable (Exch.) Mg, CEC with OM and Exch. Na and Exch. K indicating that negative charges derived from organic matter played an important role in cation retention capacity, nutrient supply, and soil fertility. The SFI analysis (9.26) in rehabilitated forest planted in year 1991 indicated greatest accumulation of organic matter from litter fall. In addition, the SEF values of the rehabilitated forests in relation to planting years indicated an undulating trend. Generally, SFI and SEF exhibit strong correlations with soil chemical and biological features, implying that these two indices can be used as indicators of soil quality.